Familial Adenomatous Polyposis with Synchronous Colorectal, Bilateral Ovarian, and Uterine Malignancies - Bipin Thomas Prasad (Oman Medical Journal, 2021)
We present a case of a 47-year-old female with three primary malignancies. This is an unusual presentation and highlights the dilemmas in the workup and formulation of treatment plans. Genetic studies to identify mutations may help explain the pathophysiology.